The Effect of Islamic Business Ethics Implementation and Product Innovation on Customer Satisfaction - Abdul Muhyi; Welly Kuswanto (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Amidst intense retail competition, business entities are required to have adaptive strategies to win the market. This study aims to deeply analyze the effect of implementing Islamic Business Ethics and product innovation on consumer satisfaction at Lirboyo Bakery, a unique representation of a pesantren-based business (Santripreneur). This research uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observation, and documentation, which were then analyzed using the Miles, Huberman, and Saldaña interactive model. The results show a holistic synergy where Islamic Business Ethics acts as a trust builder and moral filter through the principles of siddiq and ihsan, generating affective satisfaction. Meanwhile, product innovation serves as a differentiator and market relevance maintainer through variant and packaging development, leading to functional satisfaction. In conclusion, the blend of moral integrity and adaptive functional quality makes business ethics a primary non-financial competitive advantage. This research contributes to enriching Islamic economic literature by proving that the synergy of pesantren ethical values and modern innovation is key to business sustainability and comprehensive consumer satisfaction.